Death without progression as an endpoint to describe cardiac radiation effects in locally advanced non-small cell lung cancer. (March 2023) - Yegya-Raman, Nikhil; Kegelman, Timothy P.; Ho Lee, Sang; Kallan, Michael J.; Kim, Kristine N.; Natarajan, Jyotsna; Deek, Matthew P.; Zou, Wei; O'Reilly, Shannon E.; Zhang, Zheng; Levin, William; Cengel, Keith; et al.
Highlights: 13% experienced death without progression (DWP) after CRT for NSCLC. Baseline comorbidity and heart dose were associated with DWP. Dose to ventricles, but not atria, was associated with DWP. Associations with DWP were distinct from those observed with survival. Abstract: Background and purpose: Prior studies have examined associations of cardiovascular substructure dose with overall survival (OS) or cardiac events after chemoradiotherapy (CRT) for non-small cell lung cancer (NSCLC). Herein, we investigate an alternative endpoint, death without cancer progression (DWP), which is potentially more specific than OS and more sensitive than cardiac events for understanding CRT toxicity. Materials and methods: We retrospectively reviewed records of 187 patients with locally advanced or oligometastatic NSCLC treated with definitive CRT from 2008 to 2016 at a single institution. Dosimetric parameters to the heart, lung, and ten cardiovascular substructures were extracted. Charlson Comorbidity Index (CCI), excluding NSCLC diagnosis, was used to stratify patients into CCI low (0–2; n = 66), CCI intermediate (3–4; n = 78), and CCI high (≥5; n = 43) groups. Primary endpoint was DWP, modeled with competing risk regression. Secondary endpoints included OS. An external cohort consisted of 140 patients from another institution. Results: Median follow-up was 7.3 years for survivors. Death occurred in 143 patients (76.5 %), including death after progression in 118 (63.1 %) and DWP in 25 (13.4 %). On multivariable analysis, increasing CCI stratum and mean heart dose were associated with DWP. For mean heart dose ≥ 10 Gy vs < 10 Gy, DWP was higher (5-year rate, 16.9 % vs 6.7 %, p = 0.04) and OS worse (median, 22.9 vs 34.1 months, p < 0.001). Ventricle (left, right, and bilateral) and pericardial but not atrial substructure dose were associated with DWP, whereas all three were inversely associated with OS. Cutpoint analysis identified right ventricle mean dose ≥ 5.5 Gy as a predictor of DWP. In the external cohort, we confirmed an association of ventricle, but not atrial, dose with DWP. Conclusion: Cardiovascular substructure dose showed distinct associations with DWP. Future cardiotoxicity studies in NSCLC could consider DWP as an endpoint.